Development of Relay Protection of Metro Operation Control Center Power Dispatch Simulation Training System - LIU Chun-ming; LIU De-qiang; YANG Ze-ping; LUO Shi-rong (机车电传动)
In order to satisfy real-time and fidelity requirement of simulation training system relay protection of the metro operation control center (OCC) power dispatch, and also guarantee real-time requirement of power dispatch, traffic dispatch and control dispatch combined training, protection models using hierarchical thinking and all logic judgment method were studied, and the corresponding fault simulation flow was designed. Finally, the models and flow were verified by taking the simulation training system of a metro as an example.